PENGARUH BIG SNAKE AND LADDER UNTUK MENGEMBANGKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI TK ABA 12 SURABAYA - Mahmud Sanusi, Nur Avita; Endah Hendarwati; Naili Sa’ida; Tri Kurniawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The ability to read early is a very important role for the development of children of this age, especially parents and teachers, so that children are able to read optimally. Children who have reading skills will make it easier for children to receive learning, and receive information. For this reason, it is necessary to stimulate through media to be carried out during learning at school. Big Snake And Ladder media is a snake and ladder game media that has several activities that are able to stimulate the ability to read beginning in children, namely reading symbols of pictures, letters, syllables, and composing sentences from the Katta tribe which are designed so attractive by researchers to be able to attract children's attention, can be used by children in play and learning activities. This research was conducted at Kindergarten 'Aisyiyah Bustanul Athfal 12 Surabaya. The method used in this study is quantitative using a pretest-postest one group design. The data was analyzed using the wilcoxon match pair test using a sample of 20 children. The results showed that the initial reading ability in children was improved with the value of Thitung = 0 and Ttabel = 52 or Thitung ≥ Ttable with which Ho was rejected and Ha was accepted. This means that there is an influence of Big Snake And Ladder media in the ability to read beginning in 5-year-old children at Kindergarten 'Aisyiyah Bustanul Athfal 12 Surabaya. This can be proven by children who are able to read symbols, pictures, letters, syllables and compose sentences from syllables.